Ratio Analysis to Financial Distress with Profitability as a Moderation Variable - Eduard Ary Binsar Naibaho; Adeline Natasya (Universitas Muhammadiyah Malang, 2023)
Purpose: This research aims to determine the leverage effect measured by debt to asset ratio and debt to equity ratio, liquidity measured by the current ratio, sales growth, operating cash flow on financial distress with profitability measured by return on assets as a moderating variable. Methodology/approach: Research objects were 54 real estate companies registered with S&P Capital IQ 2017 – 2021. Sample selection used purposive sampling method. Data processing method uses Panel Data Regression with Random Effect Model. Findings: This study proves operating cash flow and leverage has a positive effect on financial distress, leverage and liquidity have a negative effect on financial distress. Sales growth does not affect financial distress. Other results, profitability as a moderating variable strengthens the effect of sales growth and operating cash flow on financial distress and profitability weakens effect of debt to asset ratio and liquidity on financial distress. Meanwhile, profitability does not moderate effect of leverage on financial distress. Practical implications: This research contributes to development of literature on factors influence the occurrence of financial difficulties. Practically, it has implications for companies to analyze, maintain financial ratios in a healthy condition to avoid financial difficulties. Originality/value: This study uses profitability that measured by return on assets as a moderating variable